2018
DOI: 10.1016/j.beproc.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural repertoire of termites in corpse management: A comparison between one-piece and multiple-pieces nesting termite species

Abstract: Corpse disposal is an essential adaptation to social life. This behaviour promotes nest hygiene and prevents the spread of pathogens in the colony of social insects. The current study verified the corpse management in two termite families towards cadavers of different origins. We carried out bioassays with subcolonies of Cryptotermes brevis and colonies of Cornitermes cumulans, in which corpses of termite workers from the same colony, from another colony and from another species were introduced. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Five-minute exposures produced 94.4% mortality of recipients at week 3 (Rust et al 2008). Necrophoresis is an essential characteristic of adaptation to social living, and it has been observed in subterranean and drywood termites (Neoh et al 2012a,b;da Silva et al 2018). The previous study reported that mainly the nymphs and pseudergates of C. brevis are involved in corpse management, and they can eat intercolonial and interspecific nestmates.…”
Section: Horizontal Transfer Of Fipronilmentioning
confidence: 99%
See 2 more Smart Citations
“…Five-minute exposures produced 94.4% mortality of recipients at week 3 (Rust et al 2008). Necrophoresis is an essential characteristic of adaptation to social living, and it has been observed in subterranean and drywood termites (Neoh et al 2012a,b;da Silva et al 2018). The previous study reported that mainly the nymphs and pseudergates of C. brevis are involved in corpse management, and they can eat intercolonial and interspecific nestmates.…”
Section: Horizontal Transfer Of Fipronilmentioning
confidence: 99%
“…The previous study reported that mainly the nymphs and pseudergates of C. brevis are involved in corpse management, and they can eat intercolonial and interspecific nestmates. Soldiers participate through inspection and agonism (da Silva et al 2018). Transfer of insecticides through necrophagy may increase the efficacy of control of drywood termites.…”
Section: Horizontal Transfer Of Fipronilmentioning
confidence: 99%
See 1 more Smart Citation
“…Os cupins não removem os cadáveres do ninho; em vez disso, eles podem comê-los ou enterrá-los e evitar os locais onde foram enterrados (López-Riquelme et al, 2013). C. cumulans é capaz de identificar rapidamente cadáveres exibindo repertório comportamental complexo, incluindo enterrar, comer, limpar e ignorar os cupins mortos (Silva & Costa-Leonardo, 2018). Portanto, o rápido desenvolvimento dos ácaros após a morte do cupim pode ser uma adaptação.…”
Section: Discussionunclassified